THE USE OF HEARING MEDIA IN INCREASING RESTATION STUDY BIOLOGY STUDENTS CLASS XI IPA SMA NW MATARAM SCHOOL YEAR 2020/2021 - mahnep mahnep; Raden Didi Kuswara (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
Based on experience and observation, that the biological learning process at SMA NW Mataram, generally still uses a classic approach pattern, teachers dominate the learning process by talking, reading, doing tasks and training to answer questions, while students only sit, listen, record, memorize and do problem exercises. So that the author tried alternatives in using media in the learning process, one of which was with the hearing media, namely learning with VCD aids, televisions and CD cassettes by Harun Yahya entitled